Mortar Containing Coal Bottom Ash (CBA) Treated with Citric Acid as Partial Cement Replacement - Yahya, Ahmad Asyari; Ali, Noorwirdawati; Abdul Samad, Abdul Aziz; Mohd Kamal, Nur Liyana; Shahidan, Shahiron; Abdullah, Siti Radziah (International Journal of Integrated Engineering, 2024)
The combustion process, a fundamental aspect of various industrial and energy production activities, plays a pivotal role in generating power and facilitating essential operations. While combustion is an integral part of our energy landscape, it inevitably produces a diverse range of byproducts that have far-reaching implications, for example boiler slag, coal bottom ash (CBA) and coal fly ash (FA). These byproducts have been in interest of researcher to be use as replacement materials in concrete. However, the presence of metallic elements in CBA imposes limitations on its industrial use. Extensive research has been conducted to address the issue of heavy metal amount in CBA. Past research has recommended using strong acid leaching treatment to eliminate metallic impurities from CBA. However, the employment of strong acids poses significant hazards to both human health and the environment. In this study, laboratory test indicate that acid leaching treatment has the potential to reduce metallic elements in CBA under optimum conditions, specifically at a solution temperature of 40°C with a 4% acid concentration during a 60-minute reaction period. The characteristics of CBA under optimum conditions were further determined by comparing the water consistency and setting time of untreated CBA with those of treated CBA. Additionally, mortar properties were evaluated by using 10%, 20%, and 30% cement replacement and comparing the compressive strength and water absorption results between mortar with untreated and treated CBA replacements.